From Inflation Expectations to Budget Realization: A Bibliometric Study for Designing Data-Driven Local Fiscal Strategies - Ni Luh Ayu Dessy Andriani; Putu Ayu Pramitha Purwanti; Ni Putu Wiwin Setyari (AIBPM Publisher, 2025)
This study explores the global academic landscape on inflation expectations and persistence through a bibliometric analysis aimed at informing fiscal strategy design at the subnational level. A total of 729 articles published between 2010-2025 were extracted from the Dimensions Database and analyzed using VOS Viewer. Bibliographic coupling, citation, and co-authorship analyses were conducted on the full dataset, while a filtered subset of 200 articles focusing on inflation expectations was used for keyword co-occurrence mapping. The findings indicate that the literature remains concentrated in developed economies, particularly the United States and the United Kingdom. However, emerging contributions from the Global South are gaining prominence. Thematic trends reveal growing attention to expectation anchoring, fiscal restraint, and information asymmetry, reflecting a shift toward more behavioral and institutional interpretations of inflation. Despite these developments, the incorporation of inflation expectations into local fiscal policy remains limited. Policy recommendations include integrating inflation expectations into fiscal forecasts, adopting scenario-based planning, and enhancing macroeconomic modeling capacity at the regional level. This research contributes to bridging global inflation theory with the practical needs of decentralized public finance systems.